circ_001653 Silencing Promotes the Proliferation and ECM Synthesis of NPCs in IDD by Downregulating miR-486-3p-Mediated CEMIP - Shaoqian Cui; Lei Zhang (Elsevier, 2020)
Functional changes of nucleus pulposus cells (NPCs) are considered to be the initiating factors of intervertebral disc degeneration (IDD). In this study, we investigated whether circular RNA homo sapiens (hsa)_circ_001653 (circ_001653) could bind to microRNA-486-3p (miR-486-3p) to regulate the biological properties of NPCs and the synthesis of extracellular matrix (ECM) in IDD. Initially, circ_001653 was highly expressed in isolated NPCs and degenerative NP tissues in close relation to the severity of IDD. To evaluate the effects of circ_001653 on cellular processes, we performed experiments in vitro and in vivo with altered expression of circ_001653 and miR-486-3p. An increased expression of circ_001653 in the NPCs and the degenerative NP tissues was directly associated with elevated apoptosis and an imbalance between anabolic and catabolic factors of the ECM. miR-486-3p regulated NPC proliferation and inhibited the expression of CEMIP, the cell migration-inducing hyaluronan binding protein. circ_001653 regulated miR-486-3p expression, functioning in NPCs to upregulate CEMIP, whereas circ_001653 silencing alleviated IDD in the mouse model. Altogether, circ_001653 downregulation could potentially alleviate NPC apoptosis and the metabolic imbalance of the ECM through the miR-486-3p/CEMIP axis. These mechanistic insights may present new therapeutic targets for the treatment of IDD.